Effectiveness Of Tepid Sponge Compresses And Plaster Compresses On Child Typhoid Patients with Fevers - Hastuti, Dwi; Kulsum, Dewi Ummu; Ismuhu, Siti Rahmawati; Ropei, Oop (KnE Life Sciences, 2021)
Background: Typhoid is infectious disease which is still encountered widely in various developing countries, especially those located in the tropic and subtropics. Fever is a clinincal manifestation that is often the main complaint of the sufferer. Action can be done to lower body temperature that is tepid sponge compress and plaster compress. Purpose: The purpose of this study is to determine the comparison of the effectiviness of tepid sponge compress and plaster compress of changes body temperature in school age children with typhoid fever in cibabat hospital in year 2017. Methods: The method used is quasy experiment research method with the approach of pretest and post test two design group. As many as 24 samples were taken at the patient ward of hospital Cibabat. Respondents divided into two groups namely tepid sponge compress and plaster compress by way concecutive sampling. This study was conducted for 20 minutes at each intervenstion. Data analysis used Wilcoxon test, dependen t test, and Mann-Withney. Results: Average body temperature before and after given tepid sponge compress are 38,75°C and 38,08°C with temperature different is 0,67°C. While average body temperature before and after given palster compress are 38,80°C and 38,57°C with temperature different is 0,23°C. Mann-Withney test result show that the p value = 0,000 < α = 0,05 which means bottom tepid sponge compress is more effective in lowering body temperature in scholl age children compared with plaster compress. Conclusion: Based on the result of the study, it can recommend tepid sponge compress in the implementation of nursing care to lower body temperature in typhoid fever patients. Keywords: Fever, Plaster compress, Tepid sponge